Kinerja Unit Pemotong Serasah Tebu Tipe Reel (Performance of Sugarcane Trash Cutting Unit with Reel Type Cutter): (Performance of Sugarcane Trash Cutting Unit with Reel Type Cutter) - Wahyu K. Sugandi; Radite P. A. Setiawan; Wawan Hermawan (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2016)
The problem of sugarcane trash after harvesting is experienced by the world's sugarcane plantations, including those in Indonesia. Large amount of sugarcane trash left in the field makes difficulties in soil management and plant maintenance. Current practice done by the sugarcane plantations was â€œburning before soil tillageâ€. However, the practice of burning cause unwanted impact to the environment and human health. Meanwhile, sugarcane trash still rich of nutrients for the land. The trash size is still long so that it should be reduced to improve composting process. The prototype was tested on 4 levels of reel rotational speeds and 4 levels of trash densities. During the tests, cutting torque and rotational speed of the reel were measured using a torque-meter and a digital tachometer. The prototype chopped up sugarcane trash of about 1.7 - 3.2 cm length. Higher trash density caused a higher cutting torque and cutting power, while higher rotational speed caused a lower cutting torque and a higher cutting power. The highest cutting torque was 4.03 kg.m, when chopped sugarcane trash of 32 kg/m3 in trash density on 400 rotational speed. Increasing the rotational speed caused a shorter trash size.